Chronic traumatic encephalopathy in athletes - Y. G. Yakovlenko; V. L. Fomin; N. V. Chertov; O. V. Chertov (Медицинский вестник Юга России, 2023)
The problem of chronic traumatic encephalopathy is extremely relevant from both medical and sports points of view. Unfortunately, in the domestic literature to date, this issue is not discussed enough. The consequences of repetitive mild traumatic brain injury in sports play an important social role, which determines the relevance of studying the problem and the need to develop methods for solving it. This article provides a brief review of the literature on the chronic consequences of repetitive mild traumatic brain injury in athletes predominantly in contact sports. Statistical data on the prevalence of chronic traumatic encephalopathy in professional and non-professional sports associations are given. The issue of development conditions and mechanisms of pathogenesis of the studied pathology is discussed. Changes in the substance of the brain at the microstructural level, pathological biochemical reactions and factors of genetic predisposition are described. Modern criteria for the clinical diagnosis of traumatic encephalopathy, as well as criteria for differential diagnosis with other neurodegenerative diseases, are indicated. The main pathogenetic mechanisms of the development of clinically similar, but exclusively genetically determined neurodegenerations are briefly presented. An adapted classification of concussion in athletes and criteria for returning to sports activities after a mild traumatic brain injury are given. Special attention is paid to the radiological diagnosis of traumatic encephalopathy, based on modern methods of neuroimaging, such as magnetic resonance volumetry and positron emission tomography. At the end of the article, data are presented on promising directions for the development of methods for treating the disease under study.